The Analysis on the Current Situation of the Utilization Mode of Microalgal Biomass Materials. (21st July 2022) - Zhang, Lina; Wang, Lianfeng; Nie, Huizhong; Liu, Changbin
Abstract : In recent years, global warming caused by the greenhouse effect has become one of the greatest threats to mankind. This will have a serious impact on the environment and human body, such as land desertification, increase in ocean acidity, sea level rise, and increase in pests and diseases; affect people's normal work and rest; and make people feel dizzy and nauseated. Excessive emissions of carbon dioxide (CO2 ), the main component of the greenhouse gas, have contributed to the continued rise in Earth's temperature. Although the world is vigorously developing clean energy to reduce carbon emissions, it will not replace fossil fuels in the short term. The conversion of biomass into energy is the most important way of energy utilization. Biomass energy refers to the solar energy stored in biomass in the form of chemical energy and is the fourth major energy source after oil, coal, and natural gas. At present, biofuels have gone through three developmental stages, which can be divided into first-generation biofuels, second-generation biofuels, and third-generation biofuels according to the types of raw materials and development history. The first generation of biofuels produced from food crops, such as bioethanol derived from sucrose and starch, has already entered the energy market. However, because the first generation of biofuels uses food crops as raw materials, there is a phenomenon of "competing with people for food, " and it is difficult to achieve large-scale application. To avoid the problem of food shortages, second-generation biofuels produced from nonfood crops, such as wood fiber, have been developed. Microalgae biomass energy is favored by governments and scholars all over the world because of its unique advantages of fast reproduction speed and high oil content. The cultivation of microalgae does not occupy traditional farmland, and the marginal land such as mountains, oceans, and deserts can cultivate microalgae, or develop microalgae cultivation in the air through the innovation of microalgae photosynthetic reactors. When municipal wastewater, food industry wastewater, and aquaculture wastewater are used as the medium for large-scale cultivation of microalgae, and waste gas from biogas power generation, flue gas from coal power plants, and industrial waste gas from fermentation are used as the CO2 gas source for large-scale cultivation of microalgae, it can be further reduced. The comprehensive production cost of microalgae bioenergy plays a significant emission reduction effect. Combining the above advantages, the use of microalgae to produce first- or second-generation bioenergy has become a new research direction. This study focuses on the review of microalgal biomass in fuel, nonfuel, wastewater treatment, and fuel cell.